La importancia de la tecnología en el desarrollo de América Latina y el Caribe - Vera-Vassallo, Alejandro (1995)
The article looks at three central points of discussion to do with the importance of technology in productive and business development in Latina America and the Caribbean. In the first section, the author attempts to sketch where Latin America and the Caribbean stand in terms of technological development and competitiveness in relation to other of the world´s developed and developing regions. The second section briefly highlights the features of the newly emergent world economic order, in an attempt to place the region in the present international context and proposing a number relevant suggestions for its development. In the third part, the author suggests some policies aimed at strengthening the competitiveness of the region´s companies within the framework of CEPAL´s recent proposals for “productive development with social equality”. The article winds up with a brief reference to the practices of the OCDE countries in this areas.